2018
DOI: 10.1002/star.201700110
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Starch after Extrusion: A Review

Abstract: Food extrusion has evolved over the past decades and is now a unique research area. Starch is a primary ingredient of raw materials that are widely used in food extrusion. Extrusion is a thermomechanical process that can break the bonds of starch, leading to starch gelatinization, melting, and degradation. This article reviews the effects of extrusion on structure (crystallinity, morphology, molecular weight) and physico-chemical properties (expansion ratio, water absorption index, water soluble index, texture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
126
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(133 citation statements)
references
References 63 publications
3
126
2
2
Order By: Relevance
“…Extrusion processing has been applied in the food industry for decades to manufacture cereal‐based products with distinct textural attributes, such as snacks, breakfast cereals, and instant foods . However, many extruded cereal products are perceived to have an undesirable nutritional profile because they are high in calories and fat, but low in micronutrients and nutraceuticals .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrusion processing has been applied in the food industry for decades to manufacture cereal‐based products with distinct textural attributes, such as snacks, breakfast cereals, and instant foods . However, many extruded cereal products are perceived to have an undesirable nutritional profile because they are high in calories and fat, but low in micronutrients and nutraceuticals .…”
Section: Introductionmentioning
confidence: 99%
“…Extrusion processing has been applied in the food industry for decades to manufacture cereal-based products with distinct textural attributes, such as snacks, breakfast cereals, and instant foods. [1] However, many extruded cereal products are perceived to have an undesirable nutritional profile because they are high in calories and fat, but low in micronutrients and nutraceuticals. [2] Therefore, a growing number of researches have investigated the potential of improving the nutritional profile of extruded cereal products by incorporating functional ingredients, such as fruits, [2] vegetables, [3] or edible byproducts.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular weight of the starch polymers significantly affects the physical properties of starch, such as solubility and viscosity. Therefore, determining the degree of degradation of starch during extrusion is essential for establishing processingstructure-property relationships (Ye et al, 2018). From SEC studies it has been concluded that amylopectin, not amylose, is the component most affected by extrusion processing .…”
Section: Extrusion Cookingmentioning
confidence: 99%
“…When starch is gelatinized by extrusion, its crystalline structure is disrupted due to the breaking of inter-and intra-molecular hydrogen bonds. This results in more exposed hydroxyl groups for forming hydrogen bonds with water and the presence of starch in an amorphous state (water molecules can diffuse easier) (Ye et al, 2018). Thus, WAI of extruded starch is normally higher than that of native starch, albeit it can be lower if extensive dextrinization or melting takes place (Altan, McCarthy, & Maskan, 2009;Ding, Ainsworth, Plunkett, Tucker, & Marson, 2006;Kadan, Bryant, Pepperman, 2003;Sarawong, Schoenlechner, Sekiguchi, Berghofer, & Ng, 2014).…”
Section: Physicochemical Properties Of Extruded Starches and Floursmentioning
confidence: 99%
See 1 more Smart Citation